2005
DOI: 10.1177/089686080502500212
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Open Label, Controlled Clinical Trial of Oral Administration of an Egg Albumin-Based Protein Supplement to Patients on Continuous Ambulatory Peritoneal Dialysis

Abstract: Background/Aim Malnutrition is highly prevalent in patients on continuous ambulatory peritoneal dialysis (CAPD) and is a strong predictor of increased morbidity and mortality. Therefore, the aim of this study was to evaluate the effect of oral administration of an egg albumin-based protein supplement on the nutritional status of CAPD patients. Methods In this randomized, open label, controlled clinical trial, 28 CAPD patients were allocated to a study ( n = 13) or a control ( n = 15) group. Both groups receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 23 publications
3
39
0
1
Order By: Relevance
“…The PD studies in particular highlight that protein intake cannot be considered in isolation from energy intake. Nine of the twelve PD studies detailed energy intake allowing the inclusion of this detail when generating evidence statements (Chow et al ., ; Gonzalez‐Espinoza et al ., ; Jiang et al ., a,b; Lu et al ., ; Martin‐del‐Campo & Gonzalez‐Espinoza, ; Prasad et al ., ; Sutton et al ., ; Wang et al ., ). Of the twelve HD studies only three reported energy intakes, providing insufficient evidence for the development of practice guidelines (Araujo et al ., ; Ichikawa et al ., ; Lu et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PD studies in particular highlight that protein intake cannot be considered in isolation from energy intake. Nine of the twelve PD studies detailed energy intake allowing the inclusion of this detail when generating evidence statements (Chow et al ., ; Gonzalez‐Espinoza et al ., ; Jiang et al ., a,b; Lu et al ., ; Martin‐del‐Campo & Gonzalez‐Espinoza, ; Prasad et al ., ; Sutton et al ., ; Wang et al ., ). Of the twelve HD studies only three reported energy intakes, providing insufficient evidence for the development of practice guidelines (Araujo et al ., ; Ichikawa et al ., ; Lu et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…SIGN 2− There is limited weak evidence to suggest a protein intake of 1.37 g kg −1 with a dietary energy intake of 117 kJ kg −1 (28 kcal kg −1 ) is associated with malnutrition (Chow et al ., ). SIGN 3 There is limited weak evidence to suggest that no significant difference in SGA is achieved between a protein intake of 1.0 g kg −1 and 1.7 g kg −1 per day (Gonzalez‐Espinoza et al ., ). SIGN 1− The recommendation for protein requirements of stable adults undergoing maintenance PD is provided in Table .…”
Section: Protein Requirements Of Adults Undergoing Maintenance Peritomentioning
confidence: 97%
See 1 more Smart Citation
“…In our opinion, liquid egg whites are an improvement over sports protein bars which can be used as protein and energy supplements but which are problematic for patients with dentures and which do not allow alternate preparation methods (Meade 2007). In another study, egg albumin‐powder supplementation successfully increased serum albumin in peritoneal dialysis patients but unlike liquid egg whites, the egg albumin powder did not decrease serum phosphorus levels that may be related to phosphorus‐based additives (Gonzalez‐Espinoza et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Oral supplementation with a powdered egg albumin‐based protein supplement (11 g protein twice a day) was associated with improved nutritional status in a 6‐month randomized controlled trial in 28 continuous ambulatory peritoneal dialysis (CAPD) patients (10). In the treated group, calorie intake and nitrogen appearance increased more than in the control group (541 versus 144 kCal; 0.18 versus 0.06 g/kg/day), while the frequency of moderate to severe malnutrition declined more (46% to 18% versus 33% to 27%).…”
mentioning
confidence: 99%